Combination of Fractional Exhaled Nitric Oxide (FeNO) Level and Asthma Control Test (ATC) in Detecting GINA-Defined Asthma Control in Treated Asthmatic Patients in Vietnam. (25th April 2020) - Nguyen Nhu, Vinh; Le An, Pham; Chavannes, Niels H.
Abstract : Background . FeNO has been used as a marker for Th2-mediated airway inflammation in asthma. There is evidence which recommends the use of this biomarker in asthma management. Little is known about whether the FeNO test alone or in combination with the ACT score can reflect asthma control in Vietnamese patients. Materials and Methods . A cross-sectional study was conducted in asthmatic patients (≥18 years old) recruited at the University Medical Center, Ho Chi Minh City, Vietnam from March 2016 to March 2017. Asthma control levels were assessed following the GINA 2017 guidelines, and FeNO was measured by a Niox Mino device. FeNO cut-offs predicting asthma control status were determined using the ROC curve analysis. The combination of FeNO and ACT was investigated in detecting well-controlled and uncontrolled asthma. The results of the study are as follows: 278 patients with 68% females, mean age of 44 years, and mean asthma duration of 10 years were analyzed. All patients were treated following step 2 to 4 of GINA guidelines. Mean (SD) FeNO was 30.6 (24) ppb. Patients with uncontrolled (16%), partly controlled (29%), and well-controlled asthma (55%) had a median (IQR) FeNO of 50.0 (74), 25.0 (23), and 21.0 (22.3) ppb, respectively, and the mean of FeNO in the uncontrolled group was significantly higher than that in other groups (p < 0.001 ). The area under the ROC curve (AUC) for FeNO detecting uncontrolled asthma was 0.730 with an optimal cut-off point of FeNO > 50 ppb, and this AUC increased to 0.89 when combining FeNO and ACT. The AUC for FeNO detecting well-controlled asthma was 0.601 with an optimal cut-off point of FeNO <25 ppb and this AUC increased to 0.78 if combining FeNO and ACT. Conclusions . FeNO can predict asthma control status with an estimated cut-off point of <25 ppb for well-controlled and >50 ppb for uncontrolled asthma. The combination of FeNO and ACT provides better information regarding asthma control than FeNO alone, and this combination is useful to predict asthma control statuses in asthmatic patients in Viet Nam.